2017
DOI: 10.1002/jcp.26009
|View full text |Cite
|
Sign up to set email alerts
|

MSCs ameliorates DPN induced cellular pathology via [Ca2+]i homeostasis and scavenging the pro‐inflammatory cytokines

Abstract: The MSCs of various origins are known to ameliorate or modulate cell survival strategies. We investigated, whether UCB MSCs could improve the survival of the human neuronal cells and/or fibroblast assaulted with DPN sera. The results showed, the co-culture of UCB MSCs with human neuronal cells and/or fibroblasts could effectively scavenge the pro-inflammatory cytokines TNF-α, IL-1β, IFN-ɤ and IL - 12 and control the pro-apoptotic expression of p53/Bax. Further co-culture of UCB MSCs have shown to induce anti-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 62 publications
2
5
0
Order By: Relevance
“…Excessive ROS are further attributed to increased [Ca 2+ ] i levels released by the calcium store (endoplasmic reticulum (ER)) during inflammation [42]. Our previous publications on cellular and bioenergetics models [21,43,44] have shown the increase in basal [Ca 2+ ] i that, in turn, increases ROS production, as observed in our results. This may be due to mitochondrial Ca 2+ buffering action, which, in turn, resulted in ΔΨ m depolarization, promoting ROS production and subsequent apoptosis [43].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Excessive ROS are further attributed to increased [Ca 2+ ] i levels released by the calcium store (endoplasmic reticulum (ER)) during inflammation [42]. Our previous publications on cellular and bioenergetics models [21,43,44] have shown the increase in basal [Ca 2+ ] i that, in turn, increases ROS production, as observed in our results. This may be due to mitochondrial Ca 2+ buffering action, which, in turn, resulted in ΔΨ m depolarization, promoting ROS production and subsequent apoptosis [43].…”
Section: Discussionsupporting
confidence: 80%
“…Post confluence, UCB MSCs were enriched for CD73, CD29, and CD105 using positive selection magnetic-cell sorting, and purity was enumerated by acquiring in Beckman Coulter Novus flow cytometer (Indianapolis, IN, USA). The purity is determined by presence MSCs which are positive for CD105 and CD90 expression, and negative for CD34 and CD45 [21].…”
Section: Methodsmentioning
confidence: 99%
“…Molecular studies have revealed that abnormal expression of inflammatory cytokines in the microvasculature around peripheral nerves is found in DPN patients and relevant animal models. 7 , 8 The precise process by which inflammatory damage to peripheral nerves occurs requires further clarification.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic neuropathy potentiated the activity of T-type and high voltage-activated Ca 2+ channels in primary sensory neurons (30). A recent study showed that mesenchymal stem cells improved DPN by ameliorating intracellular Ca 2+ homeostasis (31). Ca 2+ signaling-associated factors in DRG neurons include several types of Ca 2+ -permeable membrane channels (32).…”
Section: Discussionmentioning
confidence: 99%